Countering (His)story: The Politics of Silence and Postcolonial Power in J.M. Coetzee’s Foe - El idrissi, Zakariae; El Falih , Tarik; El Habbouch , Layachi (International Journal of Language and Literary Studies, 2024)
This study examines Coetzee’s Foe (1987) via the lenses of intertextuality, parody, and satire, with a particular emphasis on its subversive reinvention of Defoe’s colonial story, resistance to colonial authority, and subtle reevaluation of postcolonial subjecthood. Beyond the typical examination of Foe as an intertextual antidote to Robinson Crusoe(1719), the essay digs into the subtle articulation of power inside the silence of the subaltern. It contends that the traditional categorization of the "subaltern who cannot speak" masks an active subject whose resistance is carefully woven into the textile of unspeakability. In Foe, silence transforms from mere absence to a performing act, and unspeakably develops as a poignant form of expression. Friday’s stillness is a reflection of Homi Bhabha’s "sly civility," exemplifying a post-colonial approach that allows indigenous people to manage imperial authority through silence and passivity.